Effect of carbon black powder content on thermal, physical, and mechanical properties of carbon fabric reinforced phenolic composite - Nguyen Tuan Anh,; Dinh Van, Dr Hien; Tran Ngoc Thanh,; Vu Tung Lam, (Journal of Military Science and Technology, 2022)
Using heat-resistant fiber-reinforced phenolic composite materials (carbon fiber, glass fiber, etc.) to protect the rocket motor from high temperature has confirmed its superiority thanks to its thermal insulation and high-temperature resistance. The improvement of thermal protection properties of materials to diversify the thermal protection material family is a growing trend. Accordingly, this paper focuses on determining the influence of the percentage of carbon nano powder (0-14%) on the thermal, physical and mechanical properties of carbon fiber/phenolic matrix composite (CPC) in order to find out the extent of reasonable proportion of carbon powder to improve thermal protection. The results indicated that the addition of carbon powder with a content of about 6–10% significantly improved the thermal protection efficiency of CPC materials. The determined thermophysical parameters are the basis for calculating and designing of solid rocket motor heat insulation layer.